2022
DOI: 10.1371/journal.pone.0271135
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT lung densitometry as an obstructive marker for the diagnosis of bronchiolitis obliterans in children

Abstract: The purpose of this study is to evaluate the quantitative diagnostic performance of computed tomography (CT) densitometry in pediatric patients with bronchiolitis obliterans (BO). We measured the mean lung density (MLD) and represented the difference of MLD in inspiratory and expiratory phases (MLDD), the ratio of the MLD (E/I MLD), and the relative volume percentage of lung density at 50-Hounsfield unit (HU) interval threshold (E600 to E950). We calculated the sensitivity, specificity, and diagnostic accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Recently, few studies have reported lung volume or density analysis in patients with PE using quantitative CT [ 5 7 ]. However, there still is a relative lack of comparative studies on PE, assessing lung parenchymal density in patients with many acquired pulmonary diseases such as chronic obstructive pulmonary disease and interstitial lung disease [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, few studies have reported lung volume or density analysis in patients with PE using quantitative CT [ 5 7 ]. However, there still is a relative lack of comparative studies on PE, assessing lung parenchymal density in patients with many acquired pulmonary diseases such as chronic obstructive pulmonary disease and interstitial lung disease [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%